PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN GAME WORDWALL TERHADAP KEMAMPUAN MENGANALISIS SISWA PADA MATA PELAJARAN IPAS KELAS IV SDN SIDOTOPO I/48 - Rakhmah Mahardianti, Cindy; Arif Mahya Fanny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to determine the effect of the Problem-Based Learning (PBL) model supported by the Wordwall game on the analytical skills of fourth-grade students in the IPAS subject at SDN Sidotopo I/48. This research follows a quantitative experimental design using a one-group pre-test post-test model. The study population consists of 30 fourth-grade students at SDN Sidotopo I/48, with a total sampling technique applied, meaning all 30 students were included as participants. Data collection was carried out using tests in the form of pre-tests and post-tests. The data analysis methods included normality tests, homogeneity tests, and t-tests. The normality test results, based on the Kolmogorov-Smirnov method, showed significance values of 0.182 for the pre-test and 0.056 for the post-test. The homogeneity test resulted in a value of 0.899, which indicates that the data is homogeneous as it is greater than 0.05. Meanwhile, the hypothesis test using the paired sample t-test yielded a significance value of 0.000, which is less than 0.05. This leads to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1). Therefore, it can be concluded that there is a significant impact of the Problem-Based Learning model assisted by the Wordwall game on students' analytical skills in the IPAS subject for fourth-grade students at SDN Sidotopo I/48.